Strategi Pengembangan Usaha Keripik Sambal Teri Canga Di Tengah Persaingan UMKM Sibolga - Rahma Alia (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study is motivated by the increasing role of Micro, Small, and Medium Enterprises (MSMEs) in improving community welfare amid limited employment opportunities and increasingly competitive business environments. Keripik Sambal Teri CANGA in Kota Sibolga is one of the culinary MSMEs that faces competitive challenges and therefore requires appropriate business development strategies. This study aims to analyze the business development strategies of Keripik Sambal Teri CANGA, identify the obstacles encountered, and examine the role of the local government through the Department of Cooperatives and MSMEs in supporting business development. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was conducted interactively through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that business development strategies are carried out through two main approaches: government strategies and entrepreneur strategies. The government supports MSME development through training, guidance, access to capital, promotion, and continuous assistance. Meanwhile, the entrepreneur implements strategies by maintaining product quality through the use of fresh raw materials, innovating product flavors and packaging, utilizing social media for promotion, and improving customer service to build consumer loyalty. The main obstacles faced include limited capital, limited human resource skills, simple technology usage, limited promotion, and increasingly intense business competition. Synergy between the government and entrepreneurs is a key factor in improving competitiveness and ensuring the sustainability of MSMEs.